Indoor airborne microbial load of selected offices in a tertiary institution in South-Western Nigeria (2018)
Indoor air quality (IAQ) has been identified by the Environmental Protection Agency (EPA) as one of the most urgent top five environmental risks to public health. Numerous studies have documented that sick building syndrome (SBS) is surprisingly common even in buildings without widespread complaints and its relationship with hypersensitivity disease are often associated with exposure to high concentration of airborne microbial organisms. To contribute to knowledge on IAQ, this study evaluates the levels and composition of bacterial and fungal contamination of different offices in a tertiary institution in South-western Nigeria. A cross sectional design was used to compare the indoor airborne microbial load of three categories of offices within the institution premises: the central administrative (CA), academic (AC) and work and maintenance (W&M) offices. Indoor temperature (ºC) and relative humidity (%) of the respective offices were measured using a 5-in-1 multi-tester N21FR made in China and categorized into comfort and high levels. Air samples were collected using a TE-10-890 Andersen single stage microbial air sampler and the total counts per cubic metre were compared with the American Industrial Hygiene Association guideline (AIHA). Data were analyzed using descriptive statistics, t-test, Spearman’s rank correlation and regression analysis. Offices in CA recorded the highest mean indoor Total Bacteria Count (TBC) of 22.6 ± 12.2cfu/m3 as compared to W&M (18.3 ± 10.4cfu/m3) and AC (15.6 ± 8.4cfu/m3) p<0.05. However, AC offices recorded the highest mean Total Fungi Count (TFC) of 3.6 ± 2.3cfu/m3 as compared to CA (3.5 ± 1.7cfu/m3) and W&M (3.3 ± 2.1cfu/m3) p>0.05. The indoor TBC and TFC of the categories of offices were found to be lower than the AIHA guideline limit. The number of persons at the point of sampling was found to significantly predict the level of indoor TBC, p<0.01. The most isolated bacteria were Staphylococcus spp., Streptococcus spp. and Micrococcus spp., whereas Cladosporium spp., Aspergillus spp. were the most abundant fungi isolates. The present study implicated population as a major source of microbial contamination in the office environment. Adequate knowledge about indoor air quality in terms of microbial contamination and its implication on health should be provided to staff of the institution in the hierarchy of control measures to mitigate the levels of indoor airborne microorganisms.